2019
DOI: 10.1007/s42452-019-0543-z
|View full text |Cite
|
Sign up to set email alerts
|

Influence of agriculture fertilizer for the enhanced growth and astaxanthin production from Haematococcus lacustris RRGK isolated from Himachal Pradesh, India

Abstract: In the present study, Haematococcus lacustris RRGK which is the former name of H. lacustris HPI-001 isolated from Himachal Pradesh, India, and another strain H. lacustris SAG-19a retrieved from Gottingen Culture Collection, Germany, were used. The H. lacustris SAG-19a served as a control. The both strains were grown in a Bold basal medium in which the components of NaNO 3 , K 2 HPO 4 •3H 2 O and KH 2 PO 4 were replaced with agriculture fertilizers such as NPK (17:17:17), urea (CH 4 N 2 O) and DAP (diammonium p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…Because of this, there has been an interest in testing the use of agricultural fertilizers for large-scale microalgal production, as these are relatively cheap compared to laboratory-grade chemicals and are available in large quantities. It is generally found that the use of agricultural fertilizers, such as those used in farming in general, yields production rates of biomass equal to or even better than traditional media [ 73 , 74 , 75 ] while at the same time providing equal or better production yields of the required end product [ 76 ]. This means that the use of agricultural fertilizers in microalgal production may reduce the costs of the growth medium by as much as 95% [ 77 , 78 ].…”
Section: Water and Nutrient Sourcesmentioning
confidence: 99%
“…Because of this, there has been an interest in testing the use of agricultural fertilizers for large-scale microalgal production, as these are relatively cheap compared to laboratory-grade chemicals and are available in large quantities. It is generally found that the use of agricultural fertilizers, such as those used in farming in general, yields production rates of biomass equal to or even better than traditional media [ 73 , 74 , 75 ] while at the same time providing equal or better production yields of the required end product [ 76 ]. This means that the use of agricultural fertilizers in microalgal production may reduce the costs of the growth medium by as much as 95% [ 77 , 78 ].…”
Section: Water and Nutrient Sourcesmentioning
confidence: 99%